What role does conflict play in fertilizer use and maize yield response in Nigeria? - Amare, Mulubrhan; Andam, Kwaw S.; Balana, Bedru; Olanrewaju, Opeyemi; Edeh, Hyacinth O. (International Food Policy Research Institute, 2024)
While increased use of inorganic fertilizer has been recommended to achieve increased maize productivity, studies on the effects of violent conflicts have also demonstrated the possible moderating influence of conflict on agricultural input use. However, the various pathways and extent through which affects fertilizer use and maize yield response to fertilizer use remain poorly understood. In this study, we used the ACLED geocoded longitudinal dataset based on the Nigeria LSMS-ISA panel survey to assess the impact of violent conflicts on fertilizer use and maize yield response in Nigeria. Understanding this effect of conflict on fertilizer use and maize yield response could be relevant to better understand smallholders resource use decisions in the context of other countries experiencing similar violent and serves as building block for understanding how factors outside the control of agronomic field experiments affect economic incentives for fertilizer use and yield of smallholder farmers.